(untitled) (Scientific journal of the Fergana State University, 2025)
The article highlights the role of basketball in increasing physical activity, improving mood and strengthening the psyche. Information will also be provided on the role of basketball in physical education lessons and its impact on children’s health. It shows the importance of developing physical qualities in boys with age, as well as the need to apply modern approaches and methods. The article provides specific recommendations aimed at educating and developing a healthy generation by studying the importance of basketball in physical education and health promotion.